2018
DOI: 10.15171/ijep.2018.24
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Salmonella typhi Infection Among Local Populations in Southern Benue, Nigeria

Abstract: Background Typhoid fever (enteric fever) is caused by Salmonella typhi which is solely a human pathogen with no known animal reservoir. S. typhi is a gram-negative, motile, rod-shaped and facultative anaerobic bacterium. 1 It is a non-spore forming and non-lactose fermenting bacterium. The bacterium is transmitted mainly through consumption of food and water that has been contaminated by faecal matter. 2 Clean water, good hygiene and sanitation are factors that prevent the spread of typhoid. 1,3,4 The incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…associated with intestinal and/or extra-intestinal diseases in humans and animals (Crump and Heyderman, 2015;Balasubranamian et al, 2018;Whistler et al, 2018). The sources of these salmonellae in the sampled individuals may be from contaminated food, meat/plant and/or associated products, contaminated water, and/or or human to human transmission since the hygiene of most Nigerians, including those residing in the study area, could generally be considered poor (Akinyemi et al, 2015;Crump and Heyderman, 2015;Adikwu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…associated with intestinal and/or extra-intestinal diseases in humans and animals (Crump and Heyderman, 2015;Balasubranamian et al, 2018;Whistler et al, 2018). The sources of these salmonellae in the sampled individuals may be from contaminated food, meat/plant and/or associated products, contaminated water, and/or or human to human transmission since the hygiene of most Nigerians, including those residing in the study area, could generally be considered poor (Akinyemi et al, 2015;Crump and Heyderman, 2015;Adikwu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although most non-typhoidal Salmonella (NTS) infections are self-limiting, ABR non-typhoidal salmonellae, the most frequent cause of foodborne illness in humans and animals are associated with 93.8 million cases of invasive gastroenteritis resulting in up to 35% hospitalization and 28% mortality rates per year worldwide while ABR typhoidal salmonellae are associated with 26 million cases with and without fever) is uncontrolled (Akinyemi et al, 2015;Anyanwu et al, 2017;Anibijuwon et al, 2018). Previous treatment with different types of antibacterial agents, including 3GCs and carbapenems, and visitation to hospitals, are factors that facilitate colonization of individuals by ABR salmonellae (Lugito and Cucunawangsi, 2017;Whistler et al, 2018;Adikwu et al, 2018). Animals are also important reservoirs of 3GC-and carbapenemresistant organisms (Crump and Heyderman, 2015;Whistler et al, 2018), and reports showed that these organisms are haboured by livestock in Nigeria (Jajere et al, 2015;Ejikeugwu et al, 2017;Ojo et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also high cases of drugs of questionable quality in circulation. The easy availability in the community without prescription makes the drug subject to abuse [10]. Knowledge of the local bacterial etiology and susceptibility patterns will be a useful guide in the effective and timely treatment of UTIs.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the local bacterial etiology and susceptibility patterns will be a useful guide in the effective and timely treatment of UTIs. Antibiotic therapy in the mainstay is the treatment of UTIs but unfortunately the emergence of multi-drug resistant strains of the causative organisms has become a major challenge of epidemiological importance [4] [11] [10]. The aim of the study was to determine the prevalence of uro-pathogens and in vitro susceptibility pattern to commonly used antibiotics among patients in health centres within Ugbokolo, Benue State.…”
Section: Introductionmentioning
confidence: 99%